Levan promotes antiproliferative and pro-apoptotic effects in MCF-7 breast cancer cells mediated by oxidative stress - TOKSOY ÖNER, EBRU (ELSEVIER, 2017)
Exopolysaccharides are high-valued bio-products produced by various microbial species and have been described to possess biological response modifying activities. These bio-products have been effective as therapeutic agents in various human disease conditions. The objective of this study was to examine the effects of levan (a (2 -> 6)-beta-D-fructan) produced on sucrose by the halophilic bacterium, Halomonas smyrnensis AAD6(T), in human breast cancer MCF-7 cells. MCF-7 cells were exposed to levan for 24 and 48 h. The antiproliferative activity was analyzed by the MTF assay. Oxidative stress was measured by the CM-H(2)DCFDA assay, and cell apoptosis was analyzed by the caspase-3/7 assay. Cell cycle was analyzed by flow cytometry and gene expression was determined by RT-PCR. Levan showed a time- and concentration-dependent antiproliferative activity, and this effect was associated with an increase in cell apoptosis and oxidative stress. In addition, levan increased the gene expression of p53 and p27. Here we demonstrated that levan exhibited an antiproliferative effect that was mediated by an increase in apoptosis and oxidative stress. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: (2 -> 6)-beta-D-Fructan; Apoptosis; p53; p27; Oxidative stress; FORKHEAD TRANSCRIPTION FACTOR; ANTITUMOR-ACTIVITY; MOLECULAR-WEIGHT; BETA-GLUCANS; ANTIOXIDANT; POLYSACCHARIDES; FERMENTATION; INHIBITION; INDUCTION; FAMILY